Effectiveness of Microsoft Kaizala and Google Classroom towards students’ mathematical communication skill and self-efficacy in learning statistics - Andriyani, Andriyani; Santosa, Achadi Budi; Saryadi, Wahyu (Universitas Ahmad Dahlan, 2022)
This study aims to describe the effectiveness and differences in the effectiveness of the learning platform with Google Classroom and Microsoft Kaizala in terms of self-efficacy and students' mathematical communication skills. The population of this research is the XII grade students of SMK Negeri 1 Giritronto Wonogiri which consists of sevent classes. From the existing population, two classes were taken randomly, namely twelfth grade of TKJ-I and twelfth grade of TKJ-II as research samples. Twelfth grade of TKJ-I was given treatment by learning using the Microsoft Kaizala platform, while twelfth grade of TKJ-II was given treatment using the Google Classroom platform. The research data were analyzed by statistical one sample t-test, MANOVA test with Hotelling's T2 at a significant level of 0.05 and univariate test to determine which platform is more effective. The results showed that: (1) statistical learning using the Microsoft Kaizala platform was effective in terms of mathematical communication and self-efficacy, while the Google Classroom platform was effective in terms of mathematical communication but not effective in terms of self-efficacy; (2) there is a difference in effectiveness between the Microsoft Kaizala platform and Google Classroom. The Microsot Kaizala platform is more effective than Google Classroom in terms of the mathematical communication skills of class twelfth grade students of SMK Negeri 1 Giritronto Wonogiri.